The Observation of Teaching and Assessing Strategies in Return to Onsite Learning After the Covid-19 Pandemic - Kadek Anggi Pratiwi Anugraha; Luh Putu Artini; Luh Gede Eka Wahyuni (Linguistic, English Education and Art (LEEA) Journal, 2023)
Over the years, many studies have investigated the learning strategies used by teachers, especially in learning English. The learning strategies studied are mostly seen from onsite and online learning, which recently occurred due to the outbreak of Covid-19 pandemic. However, only a few studies have discussed teachers' teaching and assessment strategies after learning are carried back to onsite learning. Therefore, this study aims to 1) observe teaching strategies in English classes during reconducted onsite learning and 2) observe assessment strategies in English classes during reconducted onsite learning. This research used qualitative research methods through classroom observation and interviews to obtain data from two high school English teachers in Buleleng, Bali. The results showed that the teacher used nine teaching strategies in the reconduct onsite learning process, including brainstorming, discussion, lecturing, independent study, assignments, quizzes or exercises, presentations, and summarizing. In addition, the teacher's assessment strategies during this transitional period are observation, assignments, and quizzes or tests. From this research, it can be concluded that teachers use various learning strategies, even though they have re-adapted to onsite learning. In addition, from the results of this study, two possible implications for teaching English were drawn. Keywords: Assessment Strategies, Onsite Learning, Teaching Strategies